Designing and implementing a Web-based real time routing service for crisis management (a case study for district 11 of Tehran) - javad sadidi; seyed hassan hosseini sajedi (تحقیقات کاربردی علوم جغرافیایی)
Timing framework associated with catastrophes is one of the most important issues in crisis management. In such cases, being immediate has a considerable importance and web based real-time routing service as an important tool has a significant role in relief operations improvement. At this study, a web-based real time routing service based on open source technology has designed for 11th district of Tehran aiming to efficiency enhancement of relief teams at emergency conditions. In this service ANP model was used to evaluate increasing interaction between the factors, and since the purpose of this study was to find the best possible routs between two nodes by non-negative weight according to the main distance factor, Dijkstra's algorithm has been chosen as a proper routing algorithm. Open source languages, format, libraries and software such as HTML, CSS, AJAX, GeoJSON, PHP, OpenLayer, PostGIS were also used to design the service and applying online weightings, blocking each piece of routes and re-routing procedure without blocked traffics, implementation of server-side processing and reducing the volume of the client-side’s operations, being under the browser’s surveillance, no need to install any software and the ability to use it on any operating system can be named. According to the obtained results, the path’s length and traffic’s volume variables have the most important role in target function formation (travel cost) therefore the specific path will be selected as the optimal path, with the minimized distance between the destination and the traffic volume. Depending on the traffic volume severity changes, the optimal extracted route will be changed and the system has such ability to apply online weighting in order to instantaneous routing to reduce losses.